49.7k views
1 vote
Solve 6x + 2 = 10 for x using the change of base formula log base b of y equals log y over log b.

−1.222
−0.715
2.778
3.285

User Jjclarkson
by
4.1k points

2 Answers

3 votes

Answer:

B

Explanation:

−0.715

User Othyn
by
4.7k points
3 votes

Answer:

-0.715

Explanation:

Take the log to the base 6, then apply your change-of-base formula.


6^(x+2)=10\\\\x+2=\log_6{10}\\\\x=\log_6{(10)}-2\\\\x=\frac{\log{10}}{\log{6}}-2\\\\x=\frac{1}{\log{6}}-2\approx -0.714903\\\\\boxed{x\approx -0.715}

User Kraz
by
5.1k points